Pelatihan Program Playing with Books Kepada Guru PAUD Banyuwangi - Safitri, Dhian Gowinda Luh; Eka Cahya Maulidiyah; Ruqoyyah Fitri; Kartika Rinakit Adhe; Wulan Patria Saroinsong (Universitas Negeri Surabaya, 2025)
This community service program is carried out to assist early childhood education institutions in Banyuwangi in developing more interactive literacy learning through the Playing with Books program. The problem encountered is the continued use of conventional methods in literacy development, where books are only read aloud using a one-way storytelling method without two-way communication between teachers and children. The goal of this program is to provide teachers with an understanding of fun literacy programs for children through the Playing with Books program. The implementation methods include planning, conducting training, and evaluation. The training was held in May 2024, involving 21 early childhood education teachers from various institutions in Banyuwangi. The results of this program indicate an improvement in teachers' understanding of more interactive and enjoyable literacy teaching methods for children.